KARAKTERISTIK SEDIMEN DAN MIKROORGANISMA PERMUKAAN DASAR LAUT PERAIRAN MADURA BAGIAN UTARA - -, Vijaya Isnaniawardhani (Bulletin of Scientific Contribution, 2012)
Characteristics of the river basin in Citanduy landslide prone areas are showing behaviors that canThe study was conducted to investigate the characteristics of the sediment, particularly sediment texture, and the amount and spread of microorganisms (nannoplankton and foraminifera) at the seafloor surface sediments of the northern waters of Madura. Karaktersistik sediment analysis is intended to determine the sediment texture, as for the analysis of microorganisms to determine the abundance, genus and species or the dominant characteristic in this area and its relation to bathymetric position on the line pantai.Analisis dab dilakukanterhadap laboratory 15sampel seabed surface waters of the North Madura, with a depth range between 5-77 m. Based on sediment texture can be seen that the sediment is composed of clay, silt and clay lanauan pasiran, which generally contains shell fragments microorganisms. On the seafloor surface sediments can be determined 20 species of nannoplankton and planktonic foraminifera and 30spesies 16spesies Benton foraminifera, with an abundance of being. Abundance and diversity increased with increasing depth nannoplanktoncenderung and proximity to the shoreline. Abundance and keanekaragamanterendah around the northern coastline of the island of Java and Madura Strait. This is probably due to the influence of antripogenik in this area. Species that were found relatively evenly and always appear in each sample was Emiliania huxleyi and Gephyrocapsa Oceanica. Gephyrocapsa is found predominantly in samples around the shoreline. Planktonic foraminifera abundance and diversity tends to increase with increasing depth and distance to the shoreline. Globigerinoides ruber is very common. Benton foraminifera dominated by Rotalina. The common genus is Ammonia, Quinqueloculina, Spiroloculina, Triloculina, Asterorotalia, Cibicides, Cancris, Elphidium, and Textularia Pseudorotalia, which tend to be more abundant at sites located in the north (away from the beach). Cibicides showed maximum abundance in the relatively distant from the coastline. Ratio of the total abundance of foraminifera plankton foraminifera tend to increase with increasing distance to the shoreline and depth.